1997
DOI: 10.4315/0362-028x-60.8.985
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbons: In Vitro Affinity for Fumonisin B1 and Relation of Adsorption Ability to Physicochemical Parameters

Abstract: In vitro affinity tests were conducted to assess the effectiveness of 19 activated carbons (ACs), hydrated sodium calcium aluminosilicate (HSCAS), and sepiolite (S) in binding fumonisin B1 (FB1) from solution. Relationships between adsorption ability and physicochemical parameters of ACs (specific surface area, iodine value, and methylene blue index) were tested. When 5 ml of a 4-μg/ml aqueous solution of FB1 was treated with 10 mg of AC, ACs adsorbed 0.46 to 100% of the FB1. HSCAS and S were not effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…(Jackson et al, 1996). Although the literature reports increasing number of chemical detoxification processes, with emphasis on the adsorption using multifunctional chelating agents (Galvano et al, 1997;Park et al, 1997), there are still doubts regarding the negative effect on nutritional and commercial value of a chelate adsorbed products. Emphasis should be given to the promising potential of strain S69, which showed an antagonistic activity associated with detoxification twice more effective than the other microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Jackson et al, 1996). Although the literature reports increasing number of chemical detoxification processes, with emphasis on the adsorption using multifunctional chelating agents (Galvano et al, 1997;Park et al, 1997), there are still doubts regarding the negative effect on nutritional and commercial value of a chelate adsorbed products. Emphasis should be given to the promising potential of strain S69, which showed an antagonistic activity associated with detoxification twice more effective than the other microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Characterized as tricarboxylated amino polyalcohol, similar to esfingosins, they cause toxicity, inducing cerebral lesion-LEME in horses, lung edema in swines, imunodepression in poultry and hepatic carcinogenicity in rats Gelderblom et al, 1991;Norred,1993). Recent works have also reported nephrosis, thrombosis, atherosclerosis and toxicosis in other animals (Norred, 1993;Galvano et al,1997). In humans, the natural occurrence was associated with oesophageal cancer in South Africa and China Rheder et al, 1992;Wang et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, several studies have shown that results obtained in vitro do not always correlate with the efficacy of binding in vivo. In vitro studies by Galvano et al (1997) show that AC has high affinity toward fumonisin B 1 ; however, an inclusion rate of 20 mg/g diet of AC to fumonisin-contaminated diets showed no protection to rats against fumonisin B 1 (Solfrizzo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tween-60 (Tween; polyoxyethylene sorbitan monostearate) belongs to the polysorbate family of surfactants used extensively in the food, cosmetic and pharmaceutical industries to solubilize essential oils into water-based products (Oser and Oser, 1956). They are also similar in structure and function to sucrose polyesters, known to interrupt the enterohepatic circulation of persistent organic pollutants by competing with intestinal micelles for lipophilic nutrients (Cooper et al, 1997;Meijer et al, 2006 Galvano et al (1997) show that AC has high affinity towards fumonisin B 1 ; however, an inclusion rate of 20 mg/g diet of AC to fumonisincontaminated diets showed no protection to rats against fumonisin B 1 (Solfrizzo et al, 2001). Therefore, as a follow up from our promising in vitro binding studies, we wanted to next determine whether adding binding agents in the diet before slaughter would decrease levels of AND and skatole in boars.…”
Section: Introductionmentioning
confidence: 99%